(untitled) (Journal of Bio-Science, 2023)
The prevalence of prostatic carcinoma is the outcome of several factors including improved awareness the general population of the significance of carcinoma of the prostate and progresses in diagnostic approaches. The PSA is a probable prostate cancer tumor marker, although it cannot distinguish prostate cancer from BPH solely. To assess the usefulness of free, total, and free/total PSA ratios in differentiating BPH and prostate cancer has been studied under this research work. The work was carried out at RMCH during April 2021 to March 2022, 350 purposively selected urology outpatients and inpatients at RMCH were studied cross-sectional study. Trans-rectal ultrasound (TRUS) and serum PSA levels were analyzed along with Digital rectal examination (DRE). A digital guided prostatic biopsy using a monopty biopsy gun confirmed the diagnosis. Data analysis was done in SPSS 26 software program. Prostatic cancer was more prevalent in men aged 70-80, whereas BPH was more common in men aged 60-70 (p = 0.00032). Histopathology revealed 95 prostate cancer patients, 82 with PSA >4 ng/ml and 85 patients had f/t PSA ratio>0.16. BPH was found in 255 individuals. 139 BPH patients had total PSA >4 ng/ml and 245 BPH patients had f/t PSA ratio ≤0.16. Total PSA had sensitivity and specificity of 86.32% and 45.49%, respectively, lower than f/t ratio. The (Positive predictive value) PPV and accuracy was significantly higher in f/t ratio than total PSA. Along with total PSA, free and free/total PSA ratio may help detect prostate cancer early and distinguish BPH from prostate cancer. J Bio-Sci. 30(1): 79-89, 2022 (June)